Design and Analysis of Algorithms. - Dave, Parag H. (1900)
Design and Analysis of Algorithms is the outcome of teaching, research and consultancy done by the authors over more than two decades. All aspects pertaining to algorithm design and algorithm analysis have been discussed over the chapters.
Objectives.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books